Religious feminists and the intersectional feminist movements: Insights from a case study. Issue 2 (May 2021) - Giorgi, Alberta
Scholars describe Global North feminisms as mostly 'secular' and often opposing religion. Contemporary feminist intersectional movements seem to offer different approaches able to overcome distances and articulate the role of religion in feminist emancipatory practice. This contribution explores the complex role of religion in intersectional feminist movements, drawing on the experiences of religious-feminist and secular-feminist women in Italy. The results highlight that religious women are increasingly part of feminist intersectional movements. Nonetheless, religious inequalities are often overlooked, and religion triggers ambivalent reactions, often resulting in a process of othering minority women.